Danas at dagok ng tokhang: state terror, gender, and the war on drugs - Mijares, Aileen May P.; Natividad, Maria Dulce F. (Quezon City Asian Center, University of the Philippines Diliman, 2023)
Duterte's War on Drugs, locally known as Tokhang (summary killngs) and patayan, has been widely criticized, with civil society and human rights groups condemning its brutality and impunity. There has been an uproar over the ruthless killings of suspected drug 'addicts' who are primarily male, from urban poor communities. With the spate of killings that strip urban poor communities of young men, the dissertation examines the class and gendered dimensions of the drug war. Using a feminist frame, the paper gives a gendered analysis of the War on Drugs, and how masculinized and militarized state agents have historically been primed for violence. It showcases women's testimonies and narratives (pagpapatotoo) as a form of truth-telling in light of the vehement denials of Extrajudicial Killings sanctioned by the state. It looks at their lived experiences (danas) of state terror and violence (dahas), mainly via the War on Drugs, and how this has impacted their political subjectivities and agency. Their narratives reveal the challenges women face in confronting state violence, literally executed by male state agents, and how state violence has reshaped sociality and community relations amid a landscape of fear. The dissertation shows the asymmetries of power between the State and its targets. Despite their precarity and vulnerability, this 'new underclass' who have been left behind, and who comprise the wid ows and orphans of the War on Drugs showed their agency by subverting state policies and practices of violence in conjunction with their mothering roles. The importance of emotions as a political resource is explicated and brings to light how women in solidarity with civil society organizations are rebuilding their lives amid the ruins of Duterte's War on Drugs. The dissertation also offers pathways for feminist praxis, and care ethics amid a virulent and precarious world.
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman.
Keywords: War on Drugs -- Philippines; Tokhang -- Philippines; Drug control -- Philippines